Análisis, modelamiento y gestión de una micro red eléctrica para edificaciones residenciales usando paneles fotovoltaicos - Vásquez Ruiz, Carlos Rodolfo (2014)
The present project announces an alternative offer to the user or owner of a residential building to the contribution of electric power using solar photovoltaic independently it’s emplacement and aesthetics, granting a possibility or change of ideology to the user not only as consumer or salesman of the electric power from the different distributors of generation that exist in the Ecuador and turns in cogeneration of his own electric power by a microgrid, allowing to reduce the consumption of energy produced by the different electrical or electronic devices that shape the residential building through the application of energy emitted by the sun with the usage of solar photovoltaic representing the renewable energy cogeneration, clean, easy installation, little maintenance; also it supports the development of intelligent networks with a better power management system or national electrification coverage.